2018
DOI: 10.1007/s00417-018-4062-1
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy study of undescribed material at the anterior lens capsule in exfoliation syndrome

Abstract: The anterior lens capsule epithelium in patients with XFS exhibits a highly irregular and rough margin on its free side, with unbound material over its membrane, which probably contributes to loose contact with the underlying lens and leads to different clinical behaviors in XFS eyes during cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
3
8
0
2
Order By: Relevance
“…TEM examination revealed similar findings to our previous studies [14, 16]. An unbound, electron-dense, microgranular, spherical material was recorded in 3 out of 7 XFS aLCs (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…TEM examination revealed similar findings to our previous studies [14, 16]. An unbound, electron-dense, microgranular, spherical material was recorded in 3 out of 7 XFS aLCs (Fig.…”
Section: Resultssupporting
confidence: 90%
“…We recently studied aLCs of XFS patients with transmission electron microscopy (TEM) for the first time in a Greek population. We have already reported novel TEM observations such as severe abnormalities of the lens epithelial cells (LECs) [14], the presence of exfoliation fibrils within the basement membrane of the aLC [15], and the presence of a new, not previously described material on the apical side of the lens epithelium, towards the lens fibers [16]. It is mainly the latter ultrastructural alterations that seem to be related to easier hydrodissection in XFS patients, as described lately [17].…”
Section: Introductionmentioning
confidence: 99%
“…The study focused on the findings in the subepithelial region of aLC, towards the lens fibers. We reported the presence of a new, not previously described, unbound material, consisting of electron-dense microgranules or larger formations, on the apical side of the lens epithelium in the XFS group [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was this observation that stimulated our recent transmission electron microscopy studies of anterior lens capsules in XFS. Transmission electron microscopic examination revealed severe abnormalities of lens epithelial cells [13], the presence of exfoliation fibrils within the basement membrane of the anterior lens capsule [18], and the presence of new, not previously described material on the apical side of the lens epithelium towards the lens fibers [12]. The lens epithelial surface exhibited a highly irregular margin, with extracellular material covering the lens epithelial cells' apical membrane in exfoliation patients.…”
Section: Discussionmentioning
confidence: 91%
“…Recent electron microscopy studies of the anterior lens capsule in patients with XFS have revealed newly described ultrastructural alterations of the lens epithelium and its apical surface towards the lens fibers, indicating a disorder of the lens's epithelial-fiber interface in XFS [12,13]. To our knowledge, there has been no report or any kind of evaluation of difficulties with hydrodissection among patients with cataract, including those with XFS.…”
Section: Introductionmentioning
confidence: 95%